Accounting in England and Scotland: 1543-1800; Double Entry in Exposition and Practice (Book). - Zen, Stephen A.; Homburger, Richard H. (The Accounting Review, 1965)
Reviews the book "Accounting in England and Scotland: 1543-1800; Double Entry in Exposition and Practice," by B.S. Yamey, H.C. Edey and Hugh W. Thomson.